Respuesta :

You are given either the x value or the y value.

Replace the x or y in the equation and solve for the missing values.

-4x + 5y = 3

First you are given x = 0:

So you have -4(0) + 5y = 3

Simplify:

0 + 5y = 3

Divide both sides by 5:

y = 3/5

Next you have x = 1:

-4(1) + 5y = 3

Simplify:

-4 + 5y = 3

Add 4 to both sides:

5y = 7

Divide both sides by 5:

y = 7/5

Third you are given y = 3

-4x + 5(3) = 3

Simplify:

-4x +15 = 3

Subtract 15 from both sides:

-4x = -12

Divide both sides by -4:

x = 3

ACCESS MORE